Survival after in-hospital cardiopulmonary resuscitation in a major referral center - Saghafinia Masoud; Motamedi Mohammad Hosein; Piryaie Mohammad; Rafati Hasan; Saghafi Abdollah; Jalali Alireza; Madani Seyed; Kolahdehi Reza (Saudi Journal of Anaesthesia, 2010)
Aim: This study was undertaken to assess the demographics, clinical parameters and outcomes of patients undergoing cardiopulmonary resuscitation (CPR), by the code blue team at our center to compare with other centers. Materials and Methods: Data were collected retrospectively from all adult patients who underwent CPR at our hospital from 2007 to 2008. CPR was performed on 290 patients and it was given 313 times. Clinical outcomes of interest were survival at the end of CPR and survival at discharge from the hospital. Factors associated with survival were evaluated via binomial and chi square-tests. Results: Of the 290 patients included, 95 patients (30.4%) had successful CPR. However, only 35 patients (12%) were alive at discharge. The majority requiring CPR were above 60 years of age (61.7%). Males required CPR more than females. There were 125 women (43.1%) and 165 males (56.9%) aged 3 to 78 (average 59.6) years. Majority (179) of the cases (61.7%) were above 60 years of age. Regarding the various wards, 54 cases (17.3%) were in the internal medicine ward, 63 cases (20.1%) in the surgery ward, 1 case (0.3%) in the clinic, 11 cases (3.5%) in the paraclinic, 116 cases (37.1%) in the emergency (ER), 55 cases (17.5%) in the Intensive Care Unit (ICU) and Coronary Care Unit (CCU), and 13 cases (4.2%) were in other wards. Cardiac massage was done in 133 cases (42.5%), defibrillation only via electroshock 3 cases (1%), and both were used in177 cases (56.5%). The ER had the most cases of CPR. Both cardiac massage and electroshock defibrillation were needed in most cases. Conclusion: In-hospital CPR for cardiopulmonary arrest was associated with 30.4% success at our center at the end of CPR but only 12% were alive at discharge. Duration of CPR> 10 minutes was predictive of significantly decreased survival to discharge.